2019
DOI: 10.1002/clc.23232
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and antiplatelet treatment of patients with non‐ST‐segment elevation myocardial infarction: Understanding and addressing the global risk‐treatment paradox

Abstract: Clinical guidelines for the treatment of patients with non‐ST‐segment elevation myocardial infarction (NSTEMI) recommend an invasive strategy with cardiac catheterization, revascularization when clinically appropriate, and initiation of dual antiplatelet therapy regardless of whether the patient receives revascularization. However, although patients with NSTEMI have a higher long‐term mortality risk than patients with ST‐segment elevation myocardial infarction (STEMI), they are often treated less aggressively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
(191 reference statements)
0
11
1
1
Order By: Relevance
“…Antiplatelets represent a first line medical therapy in ACS management and this drug class continues to evolve as novel agents with increasingly antiplatelet actions are identified. Antiplatelet drugs are focused on the inhibition of three key platelet activation pathways: thromboxane A2 generation via cyclooxygenase-1; adenosine diphosphate mediated activation of the P2Y12 receptor and thrombin mediated activation of protease activated receptor-1 [1,5]. Acetylsalicylic acid (ASA) remains the first line treatment of ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Antiplatelets represent a first line medical therapy in ACS management and this drug class continues to evolve as novel agents with increasingly antiplatelet actions are identified. Antiplatelet drugs are focused on the inhibition of three key platelet activation pathways: thromboxane A2 generation via cyclooxygenase-1; adenosine diphosphate mediated activation of the P2Y12 receptor and thrombin mediated activation of protease activated receptor-1 [1,5]. Acetylsalicylic acid (ASA) remains the first line treatment of ACS.…”
Section: Introductionmentioning
confidence: 99%
“…As yet, the underlying causes that explain this phenomenon are not fully understood, but various pathomechanisms have been proposed. Patients presenting with NSTEMI have a worse clinical risk profile (i.e., are significantly older, have a higher burden of comorbidities and a more frequently history of coronary artery disease) [ 3 , 5 ], higher rates of recurrent ischemia [ 3 ], and are less likely to receive guideline-recommended treatment strategies at discharge [ 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…In addition, the investigators propose risk-scores to predict long-term prognosis in patients after AMI, which consequently could be a step towards personalized risk-calculation, especially in patients at an increased risk. This is also of interest, as several studies have shown that NSTEMI patients are less likely to receive guideline-recommended treatment strategies and less frequently participate in cardiac rehabilitation programs [ 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…Compared to ST-segment elevation myocardial infarction (STEMI) patients, NSTEMI patients present with more heterogeneous variation in ischemic risk and comorbidities so that the risk classification has been considered as a fundamental component to select the most appropriate therapeutic strategy for NSTEMI patients [ 1 3 , 17 ]. However, in clinical practice the treatment-risk paradox is widespread [ 5 7 ], which is partly due to the suboptimal risk assessment underestimating the ischemic risk [ 18 , 19 ], especially in China [ 4 , 6 , 20 ]. In conformity with this, according to the H–L calibration plots in the present study, the GRM dramatically underestimated the in-hospital mortality and classified nearly 40% in-hospital death into the low- or medium-risk category, which may cause underuse of invasive strategy for patients at high risk [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%